Education Quality Guarantee based on the Requirements for Continuing Education - Maqsudjan Abdullaevich, Yuldashev; Dildora Turgunovna, Pulatova (International Journal of Psychosocial Rehabilitation, 2020)
This article provides information on the needs-based in-service training system for public educators. In particular, the creation of an effective system of training and mechanisms for training. The article provides an example of a needs-based in-service training system for primary school teachers. The main components and directions of the system of organization of training based on needs are revealed. The tasks of the head of the secondary school, methodologist, district (city) department of public education, and regional departments of public education are listed in the organization of such an effective system of professional development. The conclusions and recommendations made as a result of the implementation of the mechanism proposed in the article show a solution to the problem.